Perencanaan Kepala Sekolah Terhadap Pelaksanaan Manajemen Pembelajaran di SDN 135564 Kota Tanjungbalai - M. Rafiquddin Nasution; Zainul Fuad (Pascasarjana UIN Sumatera Utara, 2021)
Learning is a process of interaction between students and learning resources in an environment that is managed in order to achieve certain predetermined goals. Learning is also a process of change in personality in the form of conversation, attitudes, habits, and intelligence. These are permanent changes in behavior that occur as a result of practice or experience. The learning atmosphere is certainly a lively and fun atmosphere that is expected. While the expected learning process is an interactive, active, and participatory process.In addition, the role of the principal is also demanded in the implementation of good learning management, that is, the principal should prepare learning objectives in an operational form, then formulate learning objectives in the form of learning products, then formulate learning objectives in the form of student behavior, then formulate learning objectives in the form of student behavior. standards of behavior to be achieved, then every activity in the school contains one goal, namely learning, and finally the principal should formulate learning objectives in the conditions in which the behavior occurs